Analysis of the Accuracy of Diagnosis and Action Codification with Reconfirmation of BPJS Inpatient Patient Claims for the January-April Period of 2024 at SLG Kediri Hospital: Analisis Keakuratan Kodifikasi Diagnosis dan Tindakan dengan Konfirmasi Ulang Klaim Pasien BPJS Rawat Inap Periode Bulan Januari-April Tahun 2024 di RSUD SLG Kediri - Puspitasari, Syndia; Hidayat, Andra Dwitama; Pangestuti, Ayu (Procedia of Engineering and Life Science, 2025)
The accuracy of the coding of diagnoses and procedures is determined based on the completeness of the medical record documents. A dispute case or dispute claim is a claim submitted by a hospital that is declared Dispute by BPJS Health if there is a discrepancy or disagreement between BPJS and the hospital regarding claims involving services or clinical actions that impact payment of patient claims. Accurate disease and procedure coding is very important to support the smooth submission of health service claims health service cost claims. The purpose of this study was to analyze the accuracy of coding diagnoses and actions with reconfirmation of claims for inpatient BPJS patients for the period January-April 2024. The research method used is a case study approach. Techniques data collection techniques in the form of observation, literature study and interviews. The population in this study is the number of BPJS patient claim files returned in January-April 2024. The sample used in this study is the number of BPJS inpatient claim files that are returned with coding inaccuracies in January-April 2024. The research results show that from January to April 2024, reconfirmation of inpatient BPJS patients tends to fluctuate. The highest reconfirmation was in April with a total of 89 documents. Meanwhile, reconfirmation with the highest codification inaccuracy was in January with a total of 26 documents. This reconfirmation is sent in Excel form which must be confirmed by the hospital. From the results of the research conducted, the cause of re-confirmation of inpatient BPJS patients related to coding inaccuracies is still high. Accurate coding can minimize hospital losses and the risk of fraud in health service facilities.